The Performance of Equity Funds Compared to Random Portfolios and Selective Portfolios (Study of Indonesia Capital Market 2006-2010) - , Roh Edhi Anindita Warastri, Prof. Dr. Eduardus Tandelilin, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
One reason that attracts investors to invest in mutual funds is its capacity to reduce risk and to maximize the return. Some investors, however, still have a preference for individual investment. Performance of the funds and individual portfolios should be evaluated using the portfolio performance measures before investors decide whether they will invest their money on mutual funds, especially equity funds, or individual portfolios. Through this research, I wish to identify which one among the equity fund or random or selective individual portfolio that has better performance than the other. The research utilizes various capital market data ranging from the year 2006 through 2010. Eighteen equity funds operating since 2006 until 2010 are selected and 4 types of portfolio are developed randomly, with 18 portfolios for each type of portfolio. Four types of portfolio are Random portfolio, Selective1 portfolio, Selective2 portfolio, and Selective3 portfolio. The Selective1, Selective2, and Selective3 portfolios are developed based on stocks that have price-earnings ratios, price-to-book values, and the combination of both that are lower than the industry average. The following step is calculating beta, standard deviation, and expected return of the equity funds and portfolios as well as the market. After that, the performance of the funds and four types of portfolios will be measured and compared â based on the performance measurement indexes: Sharpe, Treynor, and Jensen index â one to another as well as to the market performance. The result of this study shows that there is enough evidence that: selective portfolios that are based on the combination of P/E ratio and PBV perform better than P/E-ratio-based selective portfolios